Primary tumor resection in colorectal cancer patients with unresectable distant metastases: a minireview - Bai, Junge; Yang, Ming; Liu, Zheng; Efetov, Sergey; Kayaalp, Cuneyt; Dulskas, Audrius; Shaw, Darcy; Wang, Xishan (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is the second most common cause of cancer-related death among both men and women worldwide and the third most common cancer overall. About 20% of patients diagnosed with CRC were discovered to have distant metastatic lesions, the majority of which were located in the liver. For the optimum treatment of CRC patients with hepatic metastases, interventional radiologists, medical oncologists, and surgeons must all collaborate. The surgical excision of the primary tumor is an important part of CRC treatment since it has been found to be curative in cases of CRC with minimal metastases. However, given the evidence to date was gathered from retrospective data, there is still controversy over the effectiveness of primary tumor resection (PTR) in improving the median overall survival (OS) and quality of life. Patients who have hepatic metastases make up a very tiny fraction of those who are candidates for resection. With a focus on the PTR, this minireview attempted to review the current advancements in the treatment options for hepatic colorectal metastatic illness. This evaluation also included information on PTR's risks when performed on individuals with stage IV CRC.